Coming out Jewish : constructing ambivalent identities - Stratton, Jon (Routledge, 2000)
Like many Jews of our generation, Jon Stratton grew up in a family more concerned about assimilation than about preserving Jewish tradition. While he could easily 'pass' among non-Jews, he found himself increasingly torn between his fear of not belonging and a deeply-felt commitment to his family's past. Coming Out Jewish examines the unique challenge of constructing an identity amid the clash between ethnicity and conformity. For many Jews, the idea of full assimilation ended with the Holocaust. But the pressure to adapt to the mainstream, Stratton eloquently argues, remains powerful, especially for those with anglicized names, assimilationist parents, a history of recent immigration, or ambivalent experiences of themselves as Jews. With reference to the work of Daniel Boyarin, Ien Ang, and Homi Bhabha, among others, Stratton offers fresh analysis on a wide range of topics, including the Jewish origins of pluralism in the US, anti-Semitism in Germany, the Jewishness of sitcoms like Seinfeld, and the Yiddishization of American culture since World War II. More than a book about Jews and Jewishness, Coming Out Jewish smartly and accurately mines the Jewish experience in the West to give voice to the issues of migration, Diaspora, assimilation and identity that affect those, displaced and 'othered', around the world.